An overview of explosion severity on dust explosion - W. Z., Wan Sulaiman; Kasmani, R. M. (Penerbit Universiti Teknologi Malaysia, 2011)
In spite of extensive research and development to prevent and mitigate dust explosions in the process industries, this phenomenon continues to represent a constant hazard to industries including manufacturing, using and handling of combustible dust material. Lack of fundamental methods in predicting the explosion severity characteristics and real dust cloud structure are recognized as a major obstacle in predicting the course and consequences of dust explosion in practice. This present paper discusses the influent factors affecting the explosion severity of the dust clouds in order to promote the advanced development for dust explosion. In addition, the impact of inerting on dust properties by using nitrogen or carbon dioxide to a level which the dust cloud can no longer propagate a self–sustained flame would also be explored.